On robustness to a topological perturbation in fluid mechanics - Abdelbari, Merwan; Nachi, Khadra; Sokołowski, Jan; Novotny, Antonio Andre (Zielona Góra: Uniwersytet Zielonogórski)
The robustness to topological perturbations in geometrical domains filled by a fluid flowing in Stokes?Darcy regime is considered. The cost functional is given by the energy dissipation in the fluid. The topological perturbation is carried out by the nucleation of an infinitesimal circular obstacle, which can be considered as a small measurement device. Our approach is based on the topological derivative method, which has been previously employed in the shape and topology optimization problems.
Keywords: topological derivative; shape optimization; optimal control; robust control